2017
DOI: 10.1002/pssb.201700074
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-driven water permeation through multilayer graphene nanosheets

Abstract: Graphene‐based membranes have been shown to exhibit excellent potential in transporting water and separating ions and contaminants. The pressure‐driven water permeation through a graphene (GE) multilayer containing slit‐like gaps in each layer is investigated using molecular dynamics simulations in the present study. The effects of the driving pressure magnitude, as well as the multilayer configuration parameters including the number of GE layers, their porous ratio, the gap width and offset, the interlayer di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 24 publications
0
6
2
Order By: Relevance
“…Different from the nearly perfect linear increment ( R 2 > 95%) of permeance through rigid membrane structures in our previous MD studies, ,, Figures a and S3 reveal apparent fluctuations for all four compositions. The fluctuations are caused by the dynamic nature of PA structures, where deformable bonds as well as the soft van der Waals and electrostatic interactions result in the flexible and transient channels. , To examine the influence of the polymer flexibility on water transport, we immobilized the PA structure by applying a spring force (spring constant of 100 kcal mol –1 Å –2 ) on the PA atoms to their initial positions.…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…Different from the nearly perfect linear increment ( R 2 > 95%) of permeance through rigid membrane structures in our previous MD studies, ,, Figures a and S3 reveal apparent fluctuations for all four compositions. The fluctuations are caused by the dynamic nature of PA structures, where deformable bonds as well as the soft van der Waals and electrostatic interactions result in the flexible and transient channels. , To examine the influence of the polymer flexibility on water transport, we immobilized the PA structure by applying a spring force (spring constant of 100 kcal mol –1 Å –2 ) on the PA atoms to their initial positions.…”
Section: Resultscontrasting
confidence: 86%
“…Different from the nearly perfect linear increment (R 2 > 95%) of permeance through rigid membrane structures in our previous MD studies, 16,18,46 Figures 6a and S3 reveal apparent fluctuations for all four compositions. The fluctuations are caused by the dynamic nature of PA structures, where deformable bonds as well as the soft van der Waals and electrostatic interactions result in the flexible and transient channels.…”
Section: Environmental Science and Technologycontrasting
confidence: 91%
“…23 NF membranes are widely applied for desalination and separation of wastewater to achieve low operation pressures and high permeation fluxes. 24 Also, the RO membrane-based separation process is the key technology consistently providing clean water because of its high performance and cost efficiency. 25 In this work, we describe the NF and RO techniques using commercial membranes for application in desalination and aqueous nuclide separation.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the behaviors of water molecules when being brought into contact with different surfaces at the atomic scale, various insights have been made via the approach of MD simulations. It has been found that many surface properties such as morphology and polarity can significantly influence the transport process , Kieu et al 2017. conducted MD simulations of water evaporation on a polar substrate of which the wettability can be adjusted.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene, a derivative of carbon, has attracted a lot of attention over the last decade, particularly in desalination and water treatment , Kieu et al 2017, Boretti et al 2018, Dao et al 2018. The combinations of high surface area, excellent thermal conductivity and strong plasmonic potential make it a promising candidate for evaporation and steam generation.…”
Section: Introductionmentioning
confidence: 99%